The Cane or “Bufo” Toad (Rhinella marina) in Florida - Audrey C. Wilson; Steven A> Johnson (EDIS, 2017)
Cane Toads are an invasive species in Florida and in many countries around the world. They have been established in Florida since the 1950s and have now spread to human-modified habitat throughout much of South and Central Florida. Cane Toads are larger and more poisonous than Florida's native toads; they can be fatal to dogs that try to eat them, and more research is necessary to understand their impacts on Florida's native species. This document covers the history of Cane Toads in Florida and how to distinguish them from native species.  It describes their ecology and impacts on both ecosystems and people. Finally, it provides advice for dealing with Cane Toads in yards and neighborhoods.